(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article is devoted to the research of different types of compoundnouninnovations, based on the material of modern Ukrainian mass media. Word-forming, semantic and stylistic peculiarities of composite neologisms have been analysed.